SISTEM INFORMASI PENITIPAN HEWAN BERBASIS WEB - Sakina Fikry Nurjannah; Novrini Hasti (JURNAL GAUNG INFORMATIKA, 2020)
Jurassic Pet Shop is a company engaged in pet care services. In the pet care process, customers must come to the pet shop to find out the availability of a cage for their pets. Likewise if they will take their pets. Therefore, the aim of this research is to create a web-based pet care information system to make it easier for customers to leave their pets and provide information about pet care. This research uses object-oriented method or object oriented programming (OOP) method, prototype system development, and analysis and design tools using UML (Unified Modeling Language). The result of this research is that customers can make pet care transactions online, and provide better quality pet care services.